Early diagnosis of neural impairment in seropositive leprosy household contacts: The experience of a reference center in Brazil - dos Santos, Diogo Fernandes; Garcia, Leonardo Peixoto; Borges, Isabella Sabião; Oliveira, Thales Junqueira; Antunes, Douglas Eulálio; Luppi, Andrea De Martino; Goulart, Isabela Maria Bernardes (Frontiers in Medicine, 2023)
Leprosy is an infectious disease that remains with a high number of new cases in developing countries. Household contacts have a higher risk for the development of the disease, but the neural impairment in this group is not well elucidated yet. Here, we measured the chance of occurrence of peripheral neural impairment in asymptomatic leprosy household contacts who present anti-PGL-I IgM seropositivity, through electroneuromyography (ENMG) evaluation. We recruited 361 seropositive contacts (SPC) from 2017 to 2021, who were subjected to an extensive protocol that included clinical, molecular, and electroneuromyographic evaluations. Our data revealed a positivity of slit skin smear and skin biopsy qPCR of 35.5% (128/361) and 25.8% (93/361) respectively. The electroneuromyographic evaluation of the SPC showed neural impairment in 23.5% (85/361), with the predominance of a mononeuropathy pattern in 62.3% (53/85). Clinical neural thickening was observed in 17.5% (63/361) of seropositive contacts, but among the individuals with abnormal ENMG, only 25.9% (22/85) presented neural thickening in the clinical exam. Ours results corroborates the need to make the approach to asymptomatic contacts in endemic countries more timely. Since leprosy in its early stages can present an indolent and subclinical evolution, serological, molecular, and neurophysiological tools are essential to break the disease transmission chain.